Using Big Books to Promote the Elementary School Students' Participation in English Classes - Elly Rosalina Susanti (Institut Agama Islam Negeri Madura, 2020)
Maintaining the students' participation in the classroom is one of the greatest challenges faced by the English teachers especially those dealing with young learners’. This research aims to find out how well big books can improve the participation of fifth-grade students of SDN Pejagan 1 Bangkalan. Classroom action research was used as the research design. This research consisted of two cycles each of which was conducted in six meetings. The data was obtained from the observation and acting steps then analyzed descriptively. The researcher collaborated with the English teacher to conduct the research. To know the students' opinions towards the use of big books, the questionnaires were given at the end of each cycle. The interview was also done to some students and the English teacher related to the use of Big Book. This research revealed that big book which was big enough so it could be seen by the whole class; has interesting story and character and has eye-catching pictures could effectively encourage the students to participate actively in the English classes. Using big books in the classroom created a non-threatening atmosphere so that the students could express their opinion and disagreement freely